2021
DOI: 10.5334/paah.108
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mental Health through Physical Activity: A Narrative Literature Review

Abstract: Regular participation in physical activity, either recreational, or planned, structured, and repetitive is capable of yielding a multitude of health-improving benefits. Traditionally, physical activity has been recognized for its robust modulatory effects on cardiometabolic, neuromusculoskeletal, and immunological health and function. However, a sufficient quantity of emerging studies lends credence to its inclusion to improving mental health, warranting consideration as an adjuvant modality in treating mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Other studies also provide support for a protective effect for those meeting physical activity guidelines [ 17 , 18 , 55 ]. Previous research has shown that physical activity may promote mental health through secretion of neurochemicals eliciting a sense of wellbeing [ 56 ], promoting self-esteem [ 57 ], and providing opportunity for positive social connections [ 58 ]. A previous longitudinal study demonstrated mental health benefits from exercise and sports only when done with others [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also provide support for a protective effect for those meeting physical activity guidelines [ 17 , 18 , 55 ]. Previous research has shown that physical activity may promote mental health through secretion of neurochemicals eliciting a sense of wellbeing [ 56 ], promoting self-esteem [ 57 ], and providing opportunity for positive social connections [ 58 ]. A previous longitudinal study demonstrated mental health benefits from exercise and sports only when done with others [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is indisputable evidence that physical activity plays an important role in the prevention of many diseases, including heart disease, obesity, some cancers, and diabetes [ 1 ] and is associated with lower mortality rates [ 2 ]. In addition, physical activity is recognised as vital in the maintenance of mental health and enhancing well-being [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For now, physical exercise has been one of the major methods to improve the body’s health [ 10 , 11 ]. However, the evidence shows a contradictory trend in the discussion about the effect of physical exercise on the dynamic redox balance.…”
Section: Introductionmentioning
confidence: 99%